2018
DOI: 10.1001/jamanetworkopen.2018.5489
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medication Intensity and Stages of Airflow Limitation With the Risk of Hospitalization or Death in Patients With Heart Failure and Chronic Obstructive Pulmonary Disease

Abstract: Key Points Question Who are the highest risk heart failure (HF) patients with chronic obstructive pulmonary disease (COPD)? Findings In this nested case-control study of more than 50 000 UK patients with HF, COPD increased the risk of hospital admission and death by more than a third, but increased risk was specific to patients receiving the most intense COPD medication regimens: triple inhaler therapy, prescribed oral corticosteroids, or oxygen therapy. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
0
22
0
4
Order By: Relevance
“…We see a stronger association between heart failure and death than the COTE study, which may be to do with differences in the populations studied, the data sources (designed study versus primary care records) or the modelling approaches used. Increased risk of mortality in individuals with both heart failure and COPD has previously been found to be associated with intense COPD treatment [ 20 ]. Our studies agree that alcohol problems, atrial fibrillation and coronary heart disease are associated with mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…We see a stronger association between heart failure and death than the COTE study, which may be to do with differences in the populations studied, the data sources (designed study versus primary care records) or the modelling approaches used. Increased risk of mortality in individuals with both heart failure and COPD has previously been found to be associated with intense COPD treatment [ 20 ]. Our studies agree that alcohol problems, atrial fibrillation and coronary heart disease are associated with mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease is prevalent in patients with HFpEF, and it is associated with adverse clinical outcomes and poor quality of life 24,25 . The efficacy and safety of cardioactive inhaled pulmonary drugs is controversial in treating HF patients with or without lung comorbidities 5,26–28 . Therefore, it is critical to identify the subjects with concomitant HF and COPD.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The efficacy and safety of cardioactive inhaled pulmonary drugs is controversial in treating HF patients with or without lung comorbidities. 5,[26][27][28] Therefore, it is critical to identify the subjects with 29 About 70.7% and 53.3% of patients with and without COPD had a H2FPEF score of 2 to 5, respectively, indicating that the majority of the study population warrants further survey for HFpEF. However, only 2.3% to 6.4% of the dyspnoeic patients, regardless of COPD had high H2FPEF score.…”
Section: The Identification and Treatment Of Concomitant Heart Failurmentioning
confidence: 99%
“…Interestingly, multiple observational studies all point in the direction of beneficial effects of cardioselective β-blockers on survival and reduction in exacerbations, and recently a large randomized controlled trial started to evaluate metoprolol among 1028 patients with COPD. 10 The study by Lawson et al 3 concluded that prescribed COPD medication intensity and FEV 1 levels provide the basis for targeting high-risk groups. Importantly, they also showed that shortacting inhaler only or monotherapy in patients with HF and without COPD was significantly associated with approximately 30% increased risk of all-cause hospitalizations, confirming that we should be careful with short-acting inhaled β-mimetics in HF.…”
Section: + Related Articlementioning
confidence: 99%
“…Overlap is large in symptoms and signs as well as in chest radiography, electrocardiography, and spirometry results. 1,2 The study by Lawson et al 3…”
mentioning
confidence: 99%